FPE scheme based on k-splits Feistel network - Jing-wei LI; Chun-fu JIA; Zhe-li LIU; Min LI (Tongxin xuebao)
The construction features and discipline of Feistel network-based FPE(format-preserving encryption)schemes were analyzed.Considering on the problem that 2-splits Feistel networks-based FPE cipher’s block size was in narrow range,a type-2 Feistel network-based FPE scheme,which was suitable for constructing FPE cipher with scalable block size,was presented.Experiment show that type-2 Feistel network is able to use small-scaled pseudorandom function to construct cipher with scalable block size and that is practical.